Pesticide Applicator Certification and Training - Frederick M. Fishel (EDIS)
Certification is a process that allows a person to qualify to use pesticides in the course of his or her occupation. In Florida, the Florida Department of Agriculture and Consumer Services (FDACS) administers the certification process. Training provides instruction on proper pesticide use and handling to individuals who want to obtain or retain certification. In Florida, UF/IFAS Extension primarily conducts pesticide training, but other associations, industry, non-profit organizations, private companies, and federal and state government agencies also provide and assist with training. This 3-page fact sheet was written by F. M. Fishel, and published by the UF Department of Agronomy, October 2013.